THE INTERPRETATION OF “PRIA PUNYA SELERA” SLOGAN USED IN GUDANG GARAM CIGARETTE ADVERTISEMENT: CRITICAL DISCOURSE ANALYSIS - PRISTA, EVA KURNIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Critical Discourse Analysis (CDA), Consumers’ Interpretation, PriaPunya Selera Slogan.  This research tries to analyze Pria Punya Selera slogan used in Gudang Garam advertisement based on three dimensions of discourse in Fairclough’s Critical Discourse Analysis (CDA) framework. It is conducted to find out: (1) the meaning of Pria Punya Selera slogan based on three dimensions of discourse in Fairclough’s model of CDA, (2) the interpretations of Gudang Garam Cigarette male consumers in Study Program of English Universitas Brawijaya towards the Pria Punya Selera slogan used in Gudang Garam advertisement, and (3) the persuasive impact of Pria Punya Selera slogan used in Gudang Garam advertisement towards the Gudang Garam cigarette male consumers in Study Program of English Universitas Brawijaya.This research uses a qualitative approach by using content or document analysis to analyze the meaning of Pria Punya Selera slogan and the consumers’ interpretation. There are two steps in collecting the data, namely observation and interview. In addition, the researcher also uses instruments such as questionnaire and interview guide to conduct this research. In analyzing the data, the researcher uses two processes, firstly analyzing the sentence of the slogan text and then analyzing the result of interview.The findings reveal that the meaning of Pria Punya Selera slogan is composed of three words which is ideologically contested and some of linguistic features which are included in it. At the level of interpretation, the main goal of text production and text interpretation of Pria Punya Selera slogan are fulfilled well, proven by the consumers’ interpretation. However, this slogan does not significantly influence the consumers since the flavor and price are the main factors influencing them in choosing their cigarette.In conclusion, this slogan does not give persuasive impact to consumers in choosing Gudang Garam cigarette, instead the consumers prefer to choose Gudang Garam cigarette based on flavor and affordable price. This slogan only gives a good and interesting impression for consumers. Finally, the researcher suggests for the next researcher enrich the field of this research and possibly explore other numerous objects with different theories of CDA. It will be very useful for the knowledge development especially in critical discourse analysis.